Sand Hill Land Dispute Conflict in Tanjung Baru Village, East Baturaja District, Ogan Komering Ulu Regency - Muhammad Nasrulloh; Komaruddin; Reni Apriani (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research stems from a land dispute in the Bukit Pasir area, Tanjung Baru Village, East Baturaja Sub-district, Ogan Komering Ulu Regency. The conflict arose due to unclear land ownership, overlapping land claims, weak land administration, and changes in land use following the termination of the partnership between the land-owning community and the company. This study utilises the theory of Agrarian Conflict from the book Towards Justice: 70 Years of Gunawan Wiradi by Endang Suhendar (2002) and the theory of Conflict Management by Siti Nurjana Batjo (2023). A qualitative method with a descriptive approach was employed, involving observation, interviews, and documentation. Research informants comprised village officials, sub-district authorities, community leaders, and landowners. According to the research findings, the lack of clarity regarding land legality and conflicting interests among the parties were factors influencing the conflict. Resolution efforts have been undertaken through mediation and communication, but the results have not been ideal due to administrative constraints and issues with the legality of land documents.